PERISTILAHAN OPERASI TANGKAP TANGAN DITINJAU DARI PRESPEKTIF KITAB UNDANG-UNDANG HUKUM ACARA PIDANA - Krisnawati, Wahyuni; Soeskandi, Hari (Journal Evidence Of Law, 2022)
The purpose of this research is to offer novelty related to the hand catch operation carried out by the corruption eradication commission. Using normative research that examines the application of norms or legal rules that are currently in effect. Through this concept, the researcher wants to review the authority of the corruption eradication commission in carrying out hand catch operation whether it is in accordance with the term caught red-handed in the criminal code of procedure law. This is done to avoid misinterpretation regarding the suitability of the two terms, considering that the sting operation carried out by the corruption eradication commission is not stated in any law and its implementation procedure. Being caught hand in the act of criminal procedure law has four provisions that determine whether the act can be caught red-handed or not, among others: the arrest of a person while committing a crime, or immediately after a while the crime was committed, or a moment later it is called out by the general public as the person who did it, or a moment later an object is found which is strongly suspected to have been used to commit the crime, indicating that he is the perpetrator or has participated in or assisted in committing the crime. So, through a review of the two terms, it can be concluded that the hand catch operation carried out by the corruption eradication commission is in accordance with being caught red-handed as stated in the criminal procedure code.